Studi Pengendalian banjir Kota Bangkinang Sisi barat - Kurniawan, R Putra; Mudjiatko, Mudjiatko; Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Most of surface run off in rainy season in west Bangkinang city flow to Petai I river, so that Petai I river unable to deliver it anymore to Kampar river, it will be flood in some region in Bangkinang city. According a concept has been developed to this condition that devides into two parts Jendral Ahmad Yani street, for the east region flow, will be directed to Petai I river and the west region will be directed to Polsek Bangkinang channel. The aim of this study is to planned drainage system and the capacity of the channel to drain surface runoff so that to overcome the happening flood and to reduces the load flow of the Petai I river. Rainfall station data of Pasar Kampar for 15 years used to determine rainfall plan by using 10 times years period and obtained rainfall plans (R24) of 136.11 mm. From the chatchment area map and rainfall plan data the area debit calculated to get dimensions of channel plan. The finding showed that the capacity of the existing channel with dimensions of 0.45 m - 3.00 m is unable to accommodate debit that occurs of 0.06 m3/sec - 3.96 m3/sec so that a new drainage system with dimensions of 0.44 m - 2.61 m which can accommodate debit of 0.06 m3/sec - 6.72 m3/sec must be planed. Key words: Flood, rain fall, drainage system, dimension channel